Implementation of Sustainable Transportation at Higher Institutions - Mashuri, Mashuri; Pujiati, Amin (Efficient: Indonesian Journal of Development Economics, 2021)
Universities have an important role in realizing sustainable development. Semarang State University and Diponegoro University are two universities in Semarang city committed to implementing sustainable development in the campus environment. This study aims to analyze the implementation of sustainable transportation at Semarang State University and Diponegoro University. This research is descriptive quantitative. Respondents took part in this study using snowball sampling techniques consisting of pedestrian paths, bike lanes, campus bus/public transportation, and parking lots at Semarang State University and Diponegoro University. Social, economic, and environmental variables become variables that are analyzed using gap analysis and scoring methods to measure the criteria for sustainable transportation implementation. The results showed that implementing sustainable transportation at Semarang State University and Diponegoro University gained a perception of 37.5%. This means that the implementation of sustainable transportation has not been optimal. Perguruan tinggi memiliki peran penting dalam mewujudkan pembangunan yang berkelanjutan. Universitas Negeri Semarang dan Universitas Diponegoro merupakan dua perguruan tinggi di Kota Semarang yang berkomitmen dalam melaksanakan pembangunan tersebut. Penelitian ini bertujuan untuk menganalisis implementasi transportasi berkelanjutan di Universitas Negeri Semarang dan Universitas Diponegoro. Penelitian ini bersifat deskriptif kuantitatif. Pengambilan responden pada penelitian ini menggunakan teknik snowball sampling yang terdiri dari pengguna jalur pejalan kaki, jalur sepeda, bus kampus/transportasi umum dan tempat parkir di Universitas Negeri Semarang dan Universitas Diponegoro. Variabel sosial, ekonomi dan lingkungan menjadi variabel yang dianalisis dengan menggunakan metode gap analisis dan skoring untuk mengukur kriteria implementasi transportasi berkelanjutan. Hasil penelitian menunjukkan bahwa implementasi transportasi berkelanjutan di Universitas Negeri Semarang dan Universitas Diponegoro memperoleh persepsi sebesar 37.5%. Hal ini berarti pelaksanaan transportasi berkelanjutan belum optimal.